The Prosperous Justice Party’s Strategic Choices in Coalition Decision-Making for the 2024 Jakarta Regional Elections - Fakhrul Firdausi; Sri Budi Eko Wardani (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
The decision by the Prosperous Justice Party (PKS) to join the Indonesia Maju Coalition (KIM) Plus to endorse Ridwan Kamil-Suswono (RIDO) in the 2024 Jakarta gubernatorial election is a strategic anomaly. As an ideologically oriented cadre party, in the three previous editions of the Jakarta gubernatorial election, PKS consistently fielded its own cadres or partnered with external figures aligned with the party’s ideological base. In fact, in early 2024, PKS had even declared the Anies Baswedan-Sohibul Iman (AMAN) ticket. This article analyzes how PKS made the strategic decision to join KIM Plus. This study employs a qualitative case study approach. Primary data was obtained through in-depth interviews with seven key informants within PKS and KIM Plus partners, supplemented by document analysis and media coverage. The strategic choice framework by Collier and Norden (1992) was applied across five dimensions: issue linkage, modification of subjective probability, changes in cost-benefit analysis, communication signal management, and threshold calculations. The research findings indicate that these five dimensions operate simultaneously. PKS’s policy shift is not merely a form of ideological abandonment, but rather an expression of bounded strategic rationality aimed at aligning ideological language with pragmatic calculations under the pressure of an extreme multiparty presidential system.